Selection of Currently Relevant Memories by the Human Posterior Medial Orbitofrontal Cortex - Schnider, Armin (J Neurosci, 2000)
We have demonstrated previously that patients producing spontaneous confabulations fail to suppress currently irrelevant memory traces, so that they act and think on the basis of a false, temporally displaced (past) reality. All spontaneous confabulators had anterior limbic damage, in particular of the orbitofrontal cortex and basal forebrain. These findings indicated that these structures are essential for distinguishing between mental representations of ongoing reality and currently irrelevant memories. In the present study, we used a similar experimental paradigm as in our clinical studies and H(2)(15)O positron emission tomography to explore the selection of currently relevant memories by the healthy human brain. Subjects were repeatedly presented with the same set of pictures, arranged in different order each time, and were requested to indicate picture recurrences within the runs. Thus, performance in the first run depended on new learning, whereas subsequent runs required the distinction between picture repetitions within the current run (“now”) and previous picture presentations in earlier runs. Whereas initial learning activated medial temporal structures, subsequent runs provoked circumscribed posterior medial orbitofrontal activation. We suggest that this area is essential for sorting out mental associations that pertain to ongoing reality.